The Effectiveness of Hop Volatile Markers for Forecasting Dry-hop Aroma Intensity and Quality of Cascade and Centennial Hops - Lafontaine, Scott R.; Pereira, Cliff B.; Vollmer, Daniel M.; Shellhammer, Thomas H. (BrewingScience, 2018)
Eighty-four individual hop samples were gathered over three harvest years to determine chemical factors in hops that serve as indicators of a hop’s aroma potential during dry-hopping. Two public American hop varieties that are important to U.S. hop farmers and used by craft brewers globally, Cascade (n = 51) and Centennial (n = 33), were evaluated. Using a constant dry-hopping rate (3.8 g/L), significantly different aroma intensities and qualities were observed across the various samples of hops within each cultivar. Multiple linear regression analysis based on the concentrations of 16 hop oil analytes identified geraniol to be more effective than total oil content in predicting Cascade aroma quality and intensity in dry-hopped beer. Centennial hops differed from Cascade in that beta-pinene was identified as being a more improved indicator of dry-hop aroma as compared to total oil content. In each hop variety, the single hop volatiles explained approximately 50 % of the variation in the sensory qualities of the dry-hopped beer, while total hop oil content explained less than 30?% of the same variation. These results suggest that the dry-hop aroma potential of different hop varieties is predicted by different hop volatiles and that total oil content is not the best indicator of a hop?s dry-hop aroma intensity or quality.